Pengaruh Aspek Keuangan dan Non Keuangan Terhadap Opini Audit Pada Pemerintah Daerah Kabupaten dan Kota di Republik Indonesia - Iswari, Yuni; Apandi, R. Nelly Nur; Widarsono, Agus (APSSAI, 2023)
The purpose of this research was to examine the influence of financial aspects (local original income [PAD] and capital expenditure [BM]) as well as non-financial or human resource aspects (dynasty politics [PD], political background [LBPol], and educational background [LBPen]) on audit opinion [OA] on district and city government in Indonesia. The data were processed using a quantitative descriptive method followed by correlation analysis. Based on data processing, it was concluded that the political dynasty variable (PD) and political background (LBPol) had an effect on audit opinion, while the variables of local revenue (PAD), capital expenditure (BM), and educational background (LBPen) had no effect on audit opinion (OA). This research uses purposive sampling with the criteria that the regional government has a percentage of achievement of own-source revenue at intervals of 50%-150%, then for the percentage of achievement of capital expenditure at intervals of 50%-100%. Therefore, for further research, it is expected to use population data. The benefits of this research are expected to be a reference for further research.